PROBLEMS AND PECULIARITIES OF THE INTEGRATION OF ETHNIC MINORITIES INTO THE ARMENIAN SOCIETY ON THE EXAMPLE OF THE ASSYRIANS - Евстратов, Антон Геннадьевич (History, Archeology and Ethnography of the Caucasus, 2022)
In the context of the current, in general, extremely problematic situation with the integration of ethnic minorities that have appeared on the territory of certain countries, both as a result of recent migrations (European countries) and traditionally living on their territory (the states of the post-Soviet space, Asia, and also, with some reservations, USA), the positive experience in this regard looks especially relevant. Armenia, being presented in common discourse as a mono-ethnic state, however, not only has a number of ethnic minorities on its territory, but also is the very example of their successful integration within the framework of a single social structure and a single state. In this regard, the relevance of our research is seen in understanding the self-identification and self-perception of the ethnic minorities of the Republic of Armenia in this capacity, on the one hand, and as citizens of the republic, on the other. We have studied this problem through consideration of the self-description of these communities and their historical memory. This research, being part of a larger project, is directly dedicated to the self-identification of the Assyrian ethnic minority of the Republic of Armenia. As sources, the author used interviews with secular and religious leaders of the Assyrian community in Armenia (see “Applications”), as well as publications in the media and thematic publics of the community on social networks.